Waste Heat to Power: Technologies, Current Applications, and Future Potential. Issue 11 (7th September 2020) - Garofalo, Erik; Bevione, Matteo; Cecchini, Luca; Mattiussi, Fabio; Chiolerio, Alessandro
Abstract : Energy consumption, environmental impact, and sustainability have risen fast through the ranks, achieving the first places in driving investments, policies, and concerns of all countries at any developmental stage. Energy transformation, though, must cope with nonunitary efficiency of devices and processes, which results in a distributed production of waste heat. A reduction of emissions, implying a conversion of waste heat to more noble forms of energy and a concurrent increase in efficiency of the same devices and processes, is of paramount importance. In view of the enthalpy content and distribution of the different sources of waste heat, low‐grade/low‐enthalpy sources below 200 °C are considered the most fertile field for research and development, with an impressive industrial growth rate. Thermodynamic cycles and thermal conversion devices based on the most relevant physical effects are herein introduced and briefly described, including both solutions that already achieved industrial maturity and less developed systems and devices whose study is still in progress. A specific focus on three application domains, selected due to their economic relevance, is done: industrial processes for the vast energy and capital availability, automotive sector for its permeation, and wearable devices for the market size. Limits and opportunities are critically discussed. Abstract : The state‐of‐the‐art of waste heat to power solutions and applications in industrial, automotive, and wearable fields is discussed herein. Current and emerging technologies are presented. Each sector is analyzed and the most interesting and promising implementations are proposed. Finally, a comparison in terms of temperature range, efficiency, delivered power, and installation cost is conducted.